2008
DOI: 10.1080/13697130802471058
|View full text |Cite
|
Sign up to set email alerts
|

Low- and standard-estrogen dosage in oral therapy: dose-dependent effects on insulin and lipid metabolism in healthy postmenopausal women

Abstract: The oral low dose of unopposed estradiol therapy had a favorable effect on glycoinsulinemic metabolism in healthy postmenopausal women; however, the standard dose caused a slight but significant deterioration in insulin sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 53 publications
3
10
0
3
Order By: Relevance
“…Conversely, the presence of a significant increase of insulin uptake (FHIE) was evidence of greater hepatic involvement. Overall, E 2 /DRSP combination therapy as compared with E 2 -only treatment (per the results of our previous study [7]) seems to have lower…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Conversely, the presence of a significant increase of insulin uptake (FHIE) was evidence of greater hepatic involvement. Overall, E 2 /DRSP combination therapy as compared with E 2 -only treatment (per the results of our previous study [7]) seems to have lower…”
Section: Discussionsupporting
confidence: 76%
“…Our previous work showed that unopposed 1 mg/d E 2 therapy resulted in improvement of peripheral insulin sensitivity and at the same time had no hepatic and pancreatic effect (7). However, the E 2 /DRSP association seem to show minimal changes result in peripheral insulin sensitivity (tested by indexes such as M and HOMA).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The unfavorable increase in TG induced by that regimen has been shown to be attenuated by lowering the dose of CE to 0.3 mg, although this is done at the expense of the HDL-C increase [16]. The same trend was shown for unopposed oral mE 2 , which elevates TG and HDL-C when administered at the standard dose (2.0 mg) but does not change either at a low dose (1.0 mg) [17]. Wakatsuki et al [18] showed that transdermal estradiol administration lowers the serum TG level and increases the LDL size, whereas oral CE elevates serum TG and reduces the LDL size, resulting in increased susceptibility of the particles to oxidation.…”
Section: Discussionmentioning
confidence: 79%